Emerging Intentionality in Routine Dynamics: A Pragmatist View - Dittrich, Katharina; Seidl, David (Academy of Management Journal, 2018)
This paper responds to recent interest in the role of intentionality in the internal dynamics of routines. Previous research has focused on how routine participants bring particular intentions to the performance of a routine and choose the means for accomplishing the pre-defined ends accordingly. Drawing on the pragmatist theory of action and a yearlong ethnographic study of a pharmaceutical company, we uncover “emerging intentionality” in routine performances. We show how the foregrounding of means within the concrete situation at hand might lead to the emergence of new ends to pursue. Moreover, we find that the emergence of new ends in routine performances might result in updating the goals for the routine and its associated patterns. With these findings, we contribute to a better understanding of the full spectrum of intentional action in routine dynamics, ranging from purposeful action (foregrounding ends) to purposive action (foregrounding means). This expanded perspective on intentionality in routine dynamics suggests a greater potential for continuous routine change than previous research has acknowledged.